Lyonensinols A – C, 24-Norursane-Type Triterpenoids from the Twigs and Leaves of Lyonia doyonensis and Their Potential Anti-inflammatory and PTP1B Inhibitory Activities - Zhang, Ming-Zhu; Jiang, Meng-Yuan; Kong, Ling-Ping; Liu, Cai-Ying; Kang, Huai-Xin; Liu, Ai-Hong; Wang, Bin; Mao, Shui-Chun (Planta Medica, 2023)
Lyonia doyonensis is a deciduous shrub native to high-altitude regions of Asia. So far, there is no report on any chemical and biological properties of L. doyonensis. An EtOH extract of L. doyonensis twigs and leaves showed inhibitory activities on protein tyrosine phosphatase 1B and lipopolysaccharide-induced inflammation in BV-2 microglial cells. A phytochemical investigation of this extract led to the isolation of a, so far only ambiguously described, 24-norursane-type triterpenoid, now named lyonensinol A (1), along with its two new derivatives, lyonensinols B and C (2 and 3), and six known triterpenoids (4 – 9). Their structures were elucidated by detailed analysis of spectroscopic data. A combination of chemical conversions, electronic circular dichroism, and Mo2(OAc)4-induced electronic circular dichroism was used to confirm their absolute configurations. Lyonensinols B (2) and C (3) represent the first examples of norursane-type triterpenoids acylated with a p-coumaroyl moiety. The potential anti-inflammatory and protein tyrosine phosphatase 1B inhibitory activities of all the isolates were evaluated. Compounds 3, 7, and 8 at 10 µM showed potent inhibitory activities on lipopolysaccharide-induced nitric oxide production in BV-2 microglial cells, with nitric oxide levels decreasing to 31.5, 41.9, and 27.1%, respectively, while compounds 3, 4, 7, and 8 exhibited notable inhibitory activities against protein tyrosine phosphatase 1B, with IC50 values ranging from 1.7 to 18.2 µM. Interestingly, compounds 3 and 8, bearing a C-3 trans-p-coumaroyl group, showed not only more potent anti-inflammatory effects, but also exhibited stronger protein tyrosine phosphatase 1B inhibition than their respective stereoisomers (2 and 7) with a cis-p-coumaroyl group.
Keywords: Ericaceae; Lyonia doyonensis; 24-norursane-type triterpenoids; anti-inflammatory activity; PTP1B inhibition